Pesticide residues in (treated) wastewater and products of Belgian vegetable- and potato processing companies. (October 2021) - Sayed, Akram; Chys, Michael; De Rop, Jasmine; Goeteyn, Liliane; Spanoghe, Pieter; Sampers, Imca
Abstract: Pesticides are broadly utilized in crop cultivation and could end up in wastewater of vegetable- and potato companies during water-consuming processing steps. To gain insight into the presence of pesticide residues in (waste)water of these industries, water was analysed and monitored from three vegetable- and two potato processing companies in Belgium. During one year samples were collected of water before and after primary/secondary treatment (i.e. influent and effluent) and after tertiary treatment. Next to water, also (processed) carrot and potato products were analysed. Results show that boscalid (maximum: 18.32 μg/L) and terbuthylazine (maximum: 87.99 μg/L) are predominantly present in the vegetable industry and chlorpropham (maximum: 8.80×10 6  μg/L) and terbuthylazine (maximum: 3.37×10 5  μg/L) in the potato industry. The conventional treatment techniques seem to be insufficient for the removal of pesticides. Concentrations were even higher in the effluent than in the influent. Also, tertiary treatment techniques as ultra-filtration and reverse osmosis fail to reduce all pesticides below the European potable water limit of 0.1 μg/L. To meet this standard, the development and validation of new removal techniques are essential. Regarding product samples, almost no pesticide residues exceeded the MRL. Chlorpropham concentrations were statistically confirmed to be higher in potatoes and wastewater sampled when stored potatoes are processed. Graphical abstract: Image 1 Highlights: Pesticide residues through different seasons were monitored in wastewater & products. 45 residues are quantified over all samples of vegetable/potato processing companies. Terbuthylazine, chlorpropham & boscalid are present in the highest concentrations. Conventional treatment is insufficient for the removal of pesticides in wastewater. Pesticides are still present after reverse osmosis, even above 0.1 μg/L.